SOY AS A TERRITORIAL PROJECT: PRODUCTIVE EVIDENCE AND SPATIAL EXPRESSION OF AGRARIAN HOMOGENIZATION IN IMBITUVA (PARANÁ, BRAZIL), 1995-2024 (REMUNOM, 2026)
This article analyzes the “soybeanization” of agriculture in Imbituva (Paraná, Brazil) between 1995 and 2024, articulating productive evidence (data series from IBGE and IPARDES) and spatial evidence (MapBiomas – Collection 10). Methodologically, it integrates: (i) a temporal reading of municipal productive hierarchy; (ii) productivity calculation (t/ha) by cross-referencing production (t) and area (ha); and (iii) analysis of land use and land cover transitions and comparative cartography (1995/2024), interpreted as the spatial expression of the restructuring of the used territory. The results indicate that soybean production grew by 436.5% in the period, sustained mainly by technological gains (productivity from ~1.3 to ~4.2 t/ha; +220.6%), while cultivated area increased by 66.9%. Territorially, expansion occurred predominantly through internal productive reconversion: the class “Other Temporary Crops” shrank by 93.0%, evidencing substitution within the agricultural space. Comparative cartography suggests the formation of a more continuous and dominant agrarian matrix, with a tendency toward functional homogenization, in which forest remnants and the expanding urban network assume greater relative isolation. The analysis argues that soybean expansion is linked to the municipality’s integration into long commodity circuits and exogenous command logics, producing socio-environmental hierarchies and vulnerabilities in dialogue with critical literature on agricultural modernization, territorial co-optation, and territorial use (Cunha, 1986; 2018; Santos, 2000; Santos & Silveira, 2001; Castillo & Frederico, 2010; Delgado, 2012; Oliveira, 2016).